Biorenewable carbon-supported Ru catalyst for N-alkylation of amines with alcohols and selective hydrogenation of nitroarenes. (29th July 2021) - Goyal, Vishakha; Sarki, Naina; Poddar, Mukesh Kumar; Narani, Anand; Tripathi, Deependra; Ray, Anjan; Natte, Kishore
Abstract : A renewable carbon-supported Ru catalyst (Ru/PNC-700) facilely prepared  via  simple impregnation followed by the pyrolysis process for N -alkylation of anilines with benzyl alcohol and chemoselective hydrogenation of nitroarenes. Abstract : Herein, we developed a renewable carbon-supported Ru catalyst (Ru/PNC-700), which was facilely prepared via simple impregnation followed by the pyrolysis process. The prepared Ru/PNC-700 catalyst demonstrated remarkable catalytic activity in terms of conversion and selectivity towards N -alkylation of anilines with benzyl alcohol and chemoselective hydrogenation of aromatic nitro compounds. In addition, local anesthetic pharmaceutical agents ( e.g., butamben and benzocaine), including key drug intermediates, were synthesized in excellent yields under mild conditions and in the presence of water as a green solvent. Moreover, the prepared Ru/PNC-700 catalyst could be easily recovered and reused up to five times without any apparent loss in activity and selectivity.